2019
DOI: 10.1111/jfbc.13078
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical contents, antioxidant effects, and inhibitory activities of key enzymes associated with Alzheimer's disease, ulcer, and skin disorders ofSideritis albifloraandSideritis leptoclada

Abstract: In this study, urease, tyrosinase, cholinesterase inhibitory, and antioxidant activities of various extracts of Sideritis albiflora and Sideritis leptoclada were determined together with the phytochemical contents. In addition, the fatty acid compositions and phenolic compounds were investigated by gas chromatography (GC), gas chromatography-mass spectrometry (GC-MS), and high performance liquid chromatography-diode array detector (HPLC-DAD). Rosmarinic acid and caffeic acid in both Sideritis species were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 51 publications
1
23
0
1
Order By: Relevance
“…In a follow-up study, the acetone extracts showed the highest activity in terms of antioxidant activity of both Sideritis species, while the hexane extracts exhibited superior urease inhibitory activity. Both species were found to be rich in rosmarinic and caffeic acids [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a follow-up study, the acetone extracts showed the highest activity in terms of antioxidant activity of both Sideritis species, while the hexane extracts exhibited superior urease inhibitory activity. Both species were found to be rich in rosmarinic and caffeic acids [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The highest antioxidant activity could be connected with the highest level of total phenolic and flavonoid contents. Many previous studies have proved that there is a positive relationship between the levels of total phenolic and flavonoid contents and antioxidant activity (12,18). There are studies on the antioxidant properties of A. repens and C. monogyna species in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Acetylcholinesterase (AChE), butyrylcholinesterase (BChE), urease, and tyrosinase inhibitory activities of the extracts were carried out as reported in our previous study (18). α-Amylase and α-glucosidase inhibitory activities were screened according to the method previously reported by Deveci et al (19).…”
Section: Enzyme Inhibitory Activitymentioning
confidence: 99%
“…The voucher specimens have been deposited at the herbarium of Natural Products Laboratory of Muğla Sıtkı Koçman University, Muğla, Turkey. (Deveci et al, 2018a;Yang et al, 2021) Antioxidant, anti-diabetic, antityrosinase, anticholinesterase, and cytotoxic activities (Baykan et al, 2020;Deveci et al, 2018b;Deveci et al, 2020) Antioxidant, anti-ulcer, antidiabetic, anti-tyrosinase, and anticholinesterase activities (Askun et al, 2009;Deveci et al, 2019;Deveci et al, 2020)…”
Section: Plant Materialsmentioning
confidence: 99%